Crebanine, an aporphine alkaloid, induces cancer cell apoptosis through PI3K-Akt pathway in glioblastoma multiforme - Yeh, Poh-Shiow; Liu, Chien-Te; Yu, Chia-Ying; Chang, Ya-Chuan; Lin, Shu-Yu; Li, Yun-Chen; Luan, Yu-Ze; Sung, Wen-Wei (Frontiers in Pharmacology, 2024)
Glioblastoma multiforme (GBM) is one of the most prevalent and lethal primary central nervous system malignancies. GBM is notorious for its high rates of recurrence and therapy resistance and the PI3K/Akt pathway plays a pivotal role in its malignant behavior. Crebanine (CB), an alkaloid capable of penetrating the blood-brain barrier (BBB), has been shown to have inhibitory effects on proinflammatory molecules and multiple cancer cell lines via pathways such as PI3K/Akt. This study aims to investigate the efficacy and mechanisms of CB treatment on GBM. It is the first study to elucidate the anti-tumor role of CB in GBM, providing new possibilities for GBM therapy.Through a series of experiments, we demonstrate the significant anti-survival, anticlonogenicity, and proapoptotic effects of CB treatment on GBM cell lines. Nextgeneration sequencing (NGS) is also conducted and provides a complete list of significant changes in gene expression after treatment, including genes related to apoptosis, the cell cycle, FoxO, and autophagy. The subsequent protein expressions of the upregulation of apoptosis and downregulation of PI3K/Akt are further proved. The clinical applicability of CB to GBM treatment could be high for its BBB-penetrating feature, significant induction of apoptosis, and blockage of the PI3K/Akt pathway.Future research is needed using in vivo experiments and other therapeutic pathways shown in NGS for further clinical or in vivo studies.